Immune Protection of a Helminth Protein in the DSS-Induced Colitis Model in Mice - Shao Rong Long; Shao Rong Long; Ruo Dan Liu; Deepak Vijaya Kumar; Zhong Quan Wang; Chien-Wen Su (Frontiers in Immunology, 2021)
Inflammatory bowel disease (IBD) increases the risk of colorectal cancer, and it has the potential to diminish the quality of life. Recent clinical and experimental evidence demonstrate protective aspects of parasitic helminth infection against IBD. Reports have highlighted the potential use of helminths and their byproducts as potential treatment for IBD. In the current study, we studied the effect of a newborn larvae-specific serine protease from Trichinella spiralis (TsSp) on the host immune and inflammatory responses. A 49-kDa recombinant TsSp (rTsSp) was expressed in Escherichia coli BL21 (DE3) and purified. The cytotoxicity of rTsSp was analyzed. The immune protective effect of rTsSp was studied by using dextran sodium sulfate (DSS)-induced mouse colitis model. The result illustrated that rTsSp has no toxic effects on cells. We further demonstrated that administration of the rTsSp without the additional adjuvant before the induction of DSS-induced colitis reduced the severity of intestinal inflammation and the disease index; it suppressed macrophage infiltration, reduced TNF-α secretion, and induced IL-10 expression. Our findings suggest therapeutic potential of rTsSp on colitis by altering the effect of macrophages. Data also suggest immunotherapy with rTsSp holds promise for use as an additional strategy to positively modulate inflammatory processes involved in IBD.